Colorectal cancer screening - McLoughlin, Monica Ramona (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2008)
Colorectal cancer is a major public health burden and is the most common cause of mortality from cancer in Europe. Over the last two decades robust evidence from randomised clinical trials and case-control series have confirmed that the mortality from colorectal cancer can be reduced by screening. The challenge over the next decade is how to implement this in clinical practice. This is what we set out to answer with this thesis. Not all individuals are equal when it comes to screening and those with a family history of colorectal cancer are at a higher risk of developing colorectal cancer. These individuals with a moderate to high family history risk merit a more intensive screening approach with colonoscopy. We examined the feasibility of setting up a family screening clinic where after consultation with the individual a colonoscopy is offered on a dedicated screening list. Colonoscopy was performed in 405 individuals and revealed adenomatous polyps in 18.3% with 2% having high grade dysplasia and 2.2% having multiple polyps. Colorectal cancer was present in 1.5%.
Keywords: Clinical Medicine, M.D.; M.D. Trinity College Dublin